2017
DOI: 10.18517/ijaseit.7.2.1004
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Heavy Metals Concentrations in Cempaka Lake, Bangi, Selangor, Malaysia

Abstract: Seven sampling stations were identified to determine the status of water quality based on heavy metals concentrations in Cempaka Lake, Bandar Baru Bangi within two sampling periods; June 2010 and August 2010. The objective of the study is to determine the seasonal variations in the lake water quality with respect to heavy metals contamination. Seven parameters of heavy metals were analyzed from the water samples, which were collected from the seven different sampling stations at the Cempaka Lake. They are Copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Lake Titiwangsa is a recreational park on a small scale, the main source of water being rainwater, thus low concentrations of heavy metals were found in this lake. On the other hand, higher concentrations of heavy metals were recorded at lakes around Miri 23 and Lake Cempaka 24 . This is not surprising as the lakes situated in Miri are in the major settlement, agricultural and industrial areas and recreational centres.…”
Section: Comparison Of Heavy Metals Concentrations Within Selected Lakesmentioning
confidence: 95%
“…Lake Titiwangsa is a recreational park on a small scale, the main source of water being rainwater, thus low concentrations of heavy metals were found in this lake. On the other hand, higher concentrations of heavy metals were recorded at lakes around Miri 23 and Lake Cempaka 24 . This is not surprising as the lakes situated in Miri are in the major settlement, agricultural and industrial areas and recreational centres.…”
Section: Comparison Of Heavy Metals Concentrations Within Selected Lakesmentioning
confidence: 95%
“…Anthropogenic such as fertilizer application, insecticide, industrial waste amongst others yields excessive inorganic nutrients such as phosphorus and nitrogen leading to eutrophication in water body (Camargo & Alonso, 2006). Excessive non-metal nutrients from land to the body bodies is the principal water quality problem affecting the quality of coral reef health and loss of its communities which in turn cause a decrease in transparency of water and increase rate of fish mortality (Smith & Schindler, 2009;Amin et al, 2018;Gasim (2008) documented the competency of seaweed in absorbing high nitrogen concentration and store in its tissue. Rathod et al (2014); Chen et al (2008) proved the mechanism involved physisorption by active site at the surface of biosorbent and hold by a chemical bond (chemisorption) while intracellular transfer is achieved by active transport followed by biotransformation and intracellular accumulation.…”
Section: Removal Of Excess Nutrientmentioning
confidence: 99%
“…Human activities in particular husbandry livestock and agriculture play an important role in contributing contamination of ground and surface water among others pollutants. Waste water of livestock contains high concentrations of ammonia nitrogen, organic and inorganic nitrogen compound, and pathogenic bacteria, reported that ground and surface water of Model Colony in which human activities associated with urbanization, mixing of sewage water in water reservoirs during rainy seasons, industrialization, and agricultural activities are extremely main sources of pollution (Gasim et al, 2009). Industrialization and emergence of urban units placed immense stress on water resources and discharge of wastewater into natural water resources that decreases ground and surface water quality (Awan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%